What will Fat Cat sit on? - Thomas, Jan, 1958- (Clarion Books, An Imprint of HarperCollinsPublishers, 2018)
When Fat Cat is looking for somewhere to sit, a group of animals is terrified at the prospect of being crushed by his imposing size, until the mouse comes up with a solution that satisfies everyone.